Design of a heat exchanger for mini adsorption refrigeration system - Zeng, Timothy Yiwen (2015)
This report seeks to document the design of the heat exchanger from preliminary ideas to the fabrication of the physical product. Experimental and computational data were collected and a maximum experimental heat transfer coefficient of 9.2kW/m2K was achieved using water as the fluid. Fluid flow in microchannel has higher overall heat transfer coefficients between the fluid and channel wall than in conventional macro sized heat exchangers. The heat exchanger utilizes copper pipes of standard dimensions commonly used in the plumbing industry arranged to produce dimensions close to microchannels. Such copper piping are commonly manufactured in six meter lengths and sold in bulk to the construction industry.Outlet temperatures of the fabricated heat exchanger were measured at varying inlet pressures and flow rates and compared with the simulation of the heat exchanger under perfect adiabatic conditions. The flow through both annuli remains laminar reaching a maximum Reynolds number of 2478 for the cold fluid and 541 for the hot fluid. The flow through the heat exchanger also remained in the developing region for a significant length of the hot fluid in the outer annulus and cold fluid in the inner annulus, utilizing the higher local convective heat transfer coefficient at the entrance region in internal forced convection theory. However, pressure losses due to pipe friction are also greater especially at higher flow rates and a balance needs to be found to suit the application of the heat exchanger. Further studies on varying the fluid to ammonia, R-134A, oil or air, under different inlet temperatures, flow rates, length of heat exchanger and using multiple modules of the heat exchanger in parallel could be conducted to provide a more holistic study.